Hendra and Nipah Virus Infection in Cultured Human Olfactory Epithelial Cells - Viktoriya Borisevich (American Society for Microbiology, 2017)
ABSTRACT Henipaviruses are emerging zoonotic viruses and causative agents of encephalitis in humans. However, the mechanisms of entry into the central nervous system (CNS) in humans are not known. Here, we evaluated the possible role of olfactory epithelium in virus entry into the CNS. We characterized Hendra virus (HeV) and Nipah virus (NiV) infection of primary human olfactory epithelial cultures. We show that henipaviruses can infect mature olfactory sensory neurons. Henipaviruses replicated efficiently, resulting in cytopathic effect and limited induction of host responses. These results show that human olfactory epithelium is susceptible to infection with henipaviruses, suggesting that this could be a pathway for neuroinvasion in humans. IMPORTANCE Henipaviruses are emerging zoonotic pathogens that can cause acute and severe respiratory and neurological disease in humans. The pathways by which henipaviruses enter the central nervous system (CNS) in humans are still unknown. The observation that human olfactory neurons are highly susceptible to infection with henipaviruses demonstrates that the olfactory epithelium can serve as a site of Henipavirus entry into the CNS.